THE CAPABILITIES OF ANGIOTENSIN CONVERTING ENZYME INHIBITORS IN CLINICAL PRACTICE: FOCUS ON VASOPROTECTION - D. B. Nebieridze; A. S. Safaryan (Столичная издательская компания, 2015)
Data of large-scale research that shows comprehensive abilities of an angiotensin converting enzyme (ACE) inhibitors in clinical practice were represented. The traditional usage of ACE inhibitors in patients with arterial hypertension and chronic heart failure has extended recently. The study results demonstrate the efficacy of ACE inhibitors in slowing down of disease progression related to atherosclerosis and prove the possibility of a new clinical approach. Evidences support new strategic abilities of a number of ACE inhibitors (ramipril, perindopril), which are associated with vasoprotection.